Metal-Free C(sp3)–S Bond Cleavage of Thioethers to Selectively Access Aryl Aldehydes and Dithioacetals - Dan Yuan; Yong Huang; Long Tang; Ke Yang (Chemistry)
Metal-free C(sp3)–S bond cleavage of thioethers was achieved using NCS as a critical additive. A wide range of arylmethyl thioethers were successfully transformed into aryl aldehydes with satisfactory yields in chloroform. Meanwhile, employing fluorobenzene as the solvent enables the selective formation of dithioacetals from arylmethyl thioethers, achieving moderate to good yields. Notably, dithioacetals were first prepared through a metal-free C(sp3)–S bond cleavage and subsequent thioacetalization process. Furthermore, these simple and efficient approaches also provide complementary strategies for accessing important aryl aldehydes and dithioacetals.